Silvio Gesell’s Theory, Negative Interest Rates and Real Estate Investment - Mirowski, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The article discusses a somewhat forgotten theory of the German economist Silvio Gesell concerning money free from interest, and even charged for its possession, i.e. the Gesell tax. The article presents the escape from money and whether investment in real estate is justified, as well as the limitations of such investment.Research Design & Methods: The author analyses the subject literature. The theoretical issues presented in S. Gesell’s source works were interpreted in the light of contemporary economic processes and theoretical studies on his work.Findings: One of the modern expressions of Gesell’s theory is negative nominal interest rates, which have become a contemporary policy tool. While until recently even the theoretical application of such a tool was rarely considered, it has now become an important consideration in the economic reality of many economies. The natural defence of those with savings is to flee money that is burdened with fees. Real estate investment is an alternative vehicle to cash, though it is not without its limitations.Implications / Recommendations: Negative nominal interest rates have become a monetary policy tool, and there are indeed conditions that justify their use. However, it is natural for those with free cash to run away from “taxed” negative cash flows into investments that will maintain the value of their capital. One such investment is investing in real estate, though it is not without its limitations.Contribution: The author discusses the Gesell tax, a rarely analysed theory that has a contemporary, practical expression. He links it with real estate, a subject that is widely discussed today.